A translation of and commentary on Yus R. Ismail’s short story “Assalamualaikum…” - Watson, C.W. (Wacana, Journal of the Humanities of Indonesia, 2025)
Yus R. Ismail is a prolific Sundanese short story writer whose stories regularly appear in Sundanese journals and newspapers. This story “Assalamualaikum…“ appeared in Pikiran Rakyat in August 2023. It is a characteristic story of his in that it takes as its starting point the everyday lives of Sundanese villagers, and yet at the same time creates an aura of mystery around their activities. Some brief introductory information is given on the origins of the Sundanese short story in the early twentieth century and its subsequent development up to the present. A translation of the story given parallel to the original Sundanese text follows. To conclude, I offer a critique of the story that deals first with its structure, and then with what I regard as stylistic literary elements that are closely related to features of the structure and grammar of Sundanese – shared to some extent with Indonesian – and to Sundanese socio-linguistic conventions. I make the point that a translation into English cannot do justice to the ambiguity of voice of the narrator in the story.